Pengaruh Work-Life Balance Terhadap Turnover Intention Melalui Stres Kerja Sebagai Variabel Mediasi Pada Karyawan PLN UP3 Malang - Virza Heppy Stevia Difatita; Mohammad Rizal; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the effect of Work-Life Balance on Turnover Intention through Job Stress as a mediating variable among employees of PLN UP3 Malang. The research employed a quantitative approach using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with the assistance of SmartPLS software. A saturated sampling technique was applied, involving all permanent employees as respondents. The results of the measurement model evaluation indicate that all indicators of Work-Life Balance, Job Stress, and Turnover Intention met the criteria for validity and reliability, making them suitable for further analysis. The structural model testing reveals that Work-Life Balance has a significant effect on Job Stress as well as on Turnover Intention. Furthermore, Job Stress is also proven to significantly influence Turnover Intention. These findings emphasize that the balance between work and personal life plays a crucial role in shaping employees’ psychological conditions and their intention to remain within the organization. Job Stress is found to mediate the relationship between Work-Life Balance and Turnover Intention, meaning that a better work-life balance can reduce stress levels, which in turn lowers employees’ intention to leave the company. Therefore, enhancing organizational policies and practices that support Work-Life Balance becomes an essential strategy for reducing Turnover Intention and creating a healthy, productive, and sustainable work environment. Keywords: Work-Life Balance, Job Stress, Turnover Intention, Mediation.